1963
DOI: 10.1111/j.1365-3180.1963.tb00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Several Herbicides*

Abstract: Summary. 1. Laboratory methods of evaluating herbicides were developed to determine their relative effectiveness as inhibitors of seed‐germination, seedling growth and juvenile plants under photosynthetic conditions. 2. Chemicals such as dinoseb, PGP and diquat were found to be very toxic to seeds, all of them having an MDso lower than 4 × 10−5 for both radish (Raphanus sativus L.) and Sudan grass (Sorghum sudanense Stapf). 3. Of the chemicals examined, the most toxic to radish seed were dinoseb, PCP, octochl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1964
1964
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Terrestrial environment Sund & Nomura (1963) reported 5-day EC 50 s for PBP, based on inhibition of seed germination, of 1.17 × 10 −4 mol/litre and 8.59 × 10 −5 mol/litre for cucumber (Raphanus sativus) and Sudan grass (Sorghum sudanese), respectively.…”
Section: 2mentioning
confidence: 99%
“…Terrestrial environment Sund & Nomura (1963) reported 5-day EC 50 s for PBP, based on inhibition of seed germination, of 1.17 × 10 −4 mol/litre and 8.59 × 10 −5 mol/litre for cucumber (Raphanus sativus) and Sudan grass (Sorghum sudanese), respectively.…”
Section: 2mentioning
confidence: 99%
“…From laboratory evaluations on the effects of various herbicides on a range of species (excluding perennial ryegrass), Sund and Nomura (1963) noted that dalapon had a relatively low level of activity during germinaation and early development. Elsewhere coleoptile growth of ryegreiss seedlings has, however, been shown to be relatively sensitive to dalapon (Hilton et at., 1959).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, Sund & Nomura (1963) described simple laboratory methods of determining phytotoxicity of many chemicals against seeds, * Published with the approval ofthe Director as Paper No. 141 ofthejournal Series ofthe Experiment Station, Hawaiian Sugar Planters' Association, Honolulu, Hawaii, seedlings and photosynthesizing plants.…”
Section: Introductionmentioning
confidence: 99%